Correlation between Head Computed Tomography Scan Examination and Cranial Index Measurement in Pediatric Hydrocephalus - Zulfariska, Nony; Anandasari, Pande Putu Yuli; Margiani, Ni Nyoman; Sitanggang, Firman Parulian; Patriawan, Putu; Widiana, I Gde Raka (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Hydrocephalus in children can inhibit child growth. However, if treated immediately, the patient will develop normal intelligence. In radiology, the most important problem is to detect hydrocephalus early. Currently, radiology examinations can detect hydrocephalus accurately with a CT scan to identify the presence of blockages and assess the degree. Skull radiography is used to assess the presence of advanced hydrocephalus. A comparison is carried out and assesses the relationship between hydrocephalus measurement on the ventricular and cranial index by scanogram. The study used a cross-sectional analytics design, using Picture Archiving and Communication System (PACS) data. There were 68 samples taken using consecutive sampling, obtaining ventricular index measurement results above 0.30, and patients under 12 years old. Spearman rank test showed a correlation between the ventricular index measurements and cranial index, with Spearman’s Rho (r) = 0.856 and p0.001 with linear equation Y= 2.973 + 0.005X. It revealed that the constant 2.973 indicated that if there is no B coefficient value, the participation value will be 2.973. Furthermore, regression coefficient X of 0.005 indicated that the participation value grows by 0.005 for every 1 addition of the B coefficient value with R2= 0.340.